Quicksilver [large type] - Koontz, Dean R. (Dean Ray), 1945- (Thorndike Press large print core series., 2022)
"Quinn Quicksilver had a happy if unexceptional life. Until the day of "strange magnetism." It compelled him to drive out to the middle of nowhere. And it practically saved his life when two government agents showed in pursuit of him. Now Quinn is on the run, fleeing for his life. During a shoot-out at a dude ranch, he finally meets his destined companions: Bridget Rainking and her grandpa Sparky, a romance novelist with an unusual past. Barreling through the Sonoran Desert, the trio is impelled by that same inexplicable magnetism. With every mile, something sinister is in the rearview--an enemy that is more than a match for Quinn"--